Assessing Actors Involvement In The Establishing Veterinary and Animal Welfare Using Network Analysis; An Evidence From West Papua, Indonesia - Bajari, Makarius; Iyai, Deny (Technium Sustainability, 2022)
The study used focus group discussion towards fourteen representing individuals, groups, and mass institutions. The queries discussed the background, resource delivery, inter-connectivity among actors, intervention, and innovation. The primary finding is that grouped actors dominated, followed by laws actors, state institutions, stakeholders, and had a positive effect due to importance. However, threats existed indirectly without a turn-back effect. The three top shared resources were 100% on time, access, and satisfaction. Actors can have long-term period programs with sustainability using neutral to substantial power resources. Actors' relationship was found in three groups.